Thoracic Empyema Secondary to Congenital Chylothorax in a 14-Month-Old Boy with Noonan Syndrome - Takeru Oikawa; Chiharu Ota; Shinya Iwasawa; Takehiko Onoki; Hideyuki Ikeda; Takushi Hanita (Hindawi Limited, 2021)
Thoracic empyema usually occurs as a complication of bacterial pneumonia, but in rare cases, it is caused by hematogenous dissemination secondary to nonpulmonary diseases. Congenital chylothorax or chylothorax in children is associated with maldevelopment of the lymphatic system, nonimmune hydrops fetalis, several syndromes including Down syndrome, Noonan syndrome, or Turner syndrome, a complication of thoracic surgery, right heart failure with high central venous pressure, or tumors. There are very few reports of empyema associated with preexisting chylothorax. In the present study, we describe a rare case of thoracic empyema associated with congenital chylothorax and supravalvular pulmonary stenosis associated with clinically diagnosed Noonan syndrome. It is necessary to closely monitor patients with chylothorax because they are at risk of developing severe lung infections, such as pleural empyema or lung abscesses.